Design of H_∞ for induction motor - Ammar issa Ismael; Lafta E. Jumaa; Nisreen Khamas (Institute of Advanced Engineering and Science, 2020)
For Induction motor is a system that works at their speed, nevertheless there are applications at which the speed operations are needed. The control of range of speed of induction motor techniques is available. The robust control is used with induction motor and the performance of the system with the controller will be improved. The mathematical model to the controller, which were coded in MATLAB. The modeling and controller will be shown by the conditions of robustness of be less than one.